229OApplication of hysterectomy in treatment of trophoblastic neoplasia. (24th November 2019) - Liu, Y; He, Y; Long, Y
Abstract: Background: Several studies have presented value of hysterectomy in GTN, however the indications of hysterectomy in their researches were not single. Pathological reports of specimen after hysterectomy were poorly analyzed in articles available. Our study aims at evaluate the efficiency of hysterectomy applied to GTN patients who had lesions confined to the wall of uterus during chemotherapy in our hospital, and analyze their pathological reports after hysterectomy. Methods: This trial involvs patients of GTN who experienced hysterectomies in our hospital from 2003 to 2016. Each of these patients accepted normative chemotherapy according to their risk score. Hysterectomy was applied during the course of chemotherapy because they had no desire to reserve fertility and lesions confined to uterus were detected by imageologic examinations. Their clinical parameters and pathological reports were collected and outcomes were traced. We also randomly choose GTN patients who had chemotherapy alone in the same period as control group to analyze chemotherapy cycles in two groups. Results: 126 GTN patients experienced hysterectomy during 2003 to 2016 in our hospital. The time period of follow-ups was 24 months to 117 months and 97(76.98%) patients finished follow-ups, with all of these 97 patients survived. 2.06% (2/97) patients experienced recurrence after closure of treatment. Chemotherapy cycles for low risk, non-metastatic patients was 5.04±1.79, while it was 6.62±2.38 in control group, with P value <0.05. Chemotherapy cycles among high risk patients and metastatic patients had no significant differences. For all of the 126 specimen after hysterectomy, vital trophoblastic cells were found in 32.54% (41/126) specimen, of which 31.71%(13/41) patients had negative serum β-HCG(<2IU/L) before hysterectomy. Conclusions: For GTN patients with lesions confined to wall of uterus, hysterectomy plus chemotherapy is a valid treatment. It can also reduce chemotherapy cycles in low risk, non-metastatic patients. Vital trophoblastic cells may be found in specimen of patients with negative serum β-HCG before hysterectomy. Legal entity responsible for the study: Yinxia Liu. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.